Increased risk of hepatocellular carcinoma in patients with traumatic liver injury: Real-world data from a nationwide population-based study. Issue 6 (11th February 2022) - Chen, Yen-Ju; Shen, Chih-Jung; Yu, Shao-Hua; Lin, Cheng-Li; Shih, Hong-Mo
Abstract : Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer globally, and liver is one of the most commonly injured organs after blunt abdominal trauma. The traumatic liver injury–HCC risk relationship remains unclear. We extracted data of patients with traumatic liver injury between 2000 and 2013 from Taiwan National Health Insurance Research Database (n = 15, 966) and those of age-, gender-, occupation-, and index year-matched individuals without traumatic liver injury from the general population (n = 63, 864). Cox proportional hazard models were employed to determine the hazard ratios (HRs) and 95% confidence intervals (CIs) for HCC occurrence in the traumatic liver injury cohort compared with that in the comparison cohort. Patients with traumatic liver injury had an increased HCC risk (adjusted HR 2.13, 95% CI 1.59–2.85); this increased risk was more pronounced within 1 year after injury (adjusted HR 8.84, 95% CI 4.29–18.2). After >1 year of injury, HCC risk remained 1.53-fold higher in patients with traumatic liver injury than in those without traumatic liver injury (95% CI 1.08–2.15). People with traumatic liver injury demonstrate a high HCC risk, particularly within the first year of the injury.